Equality of opportunity and student support schemes - Ismail, Russayani (2007)
Equality of opportunity or access to education has always been propagated as a good mechanism to reduce economic imbalances between the rich and the poor. This is due to the fact that there is a historic correlation between educational attainment and occupational opportunities. In meeting this objective, the Malaysian government has invested vast amount of fund through subsidization of education particularly in higher education. In Malaysia, public universities obtain 80-90% of their funds from government grants. Not only the government support the public higher education institutions but it also provides the student support scheme in terms of scholarships and student loans. However with the increasing costs and rapid expansion of higher education, pressure for reform in higher education financing has intensified. Heavy reliance on public funds to finance higher education no longer seems to be an ideal solution. In this regard many countries around the world resort to the concept known as cost recovery. Replacing scholarship by student loans is one of the ways on how cost recovery can be implemented. The introduction of student loans, however, if not properly formulated will discourage or deter less advantaged socio-economic groups from getting access to higher education. In this paper we will discuss some policy options with regard to student support schemes which taking into consideration both efficiency and equity issues.